Answer: 
Step-by-step explanation:
Given


is given by replacing the
by
from the 

Now,
is

Answer:
x = 4
Step-by-step explanation:
Given the 2 equations
2x - y = 11 → (1)
x + 3y = - 5 → (2)
Multiply (1) by 3 and add to (2) to eliminate the y- term
6x - 3y = 33 → (3)
Add (2) and (3) term by term to eliminate y, that is
7x = 28 ( divide both sides by 7 )
x = 4
The answer is representativeness heuristic. This is used when making decisions about the likelihood of an occasion under doubt. It is unique of a group of heuristics (simple rules leading decision or decision-making) suggested by psychologists Amos Tversky and Daniel Kahneman in the 1970s.
Answer:
multiply the legth times width
Step-by-step explanation:
The longest meter is 3.35